Screening the possible effect of a phytofabricated nanoselenium-composite from Eruca sativa extract in reducing infertility in males - Basman, Q. S.; Huda, I. A.-Q.; Shayma’a, J. A. (Regulatory Mechanisms in Biosystems, 2023)
The antifertility effects of ketoconazole can be avoided or diminished by administering nano-selenium-based-antioxidant plant extract simultaneously or sequentially. Using selenium as nanoparticles (SeNPs) is one of the essential methods for enhancing its therapeutic effects and lowering toxicities. This study aimed to analyze the changes made to the parameters of androgens, such as testosterone and gonadotropin hormones: luteinizing hormone and follicle stimulating hormones together with sperm indexes after administration of antioxidant phytofabricated nanoselenium to mitigate oxidative damage brought on by ketoconazole. In brief, 1% weight-per-volume of the extract was loaded into a solution of 10 mM sodium selenite in various ratios on a magnetic stirrer (50 °C, PH 9) in the dark for 12 hours, left for 48 hours and then sent for characterization, which was performed using ultraviolet-visible spectroscopy (UV-vis spectra), Fourier transform infrared spectroscopy (FTIR), and dynamic light scattering (DLS). Then after the selection of the solution containing the optimal fabricated selenium nanoparticles it was administered to three groups out of seven groups of albino rats with eight animals in each one as follows: Gr. A negative control (no treatment), Gr. B oral ketoconazole 50 mg/kg for fourteen days, Gr. BC, BD, BE1, BE2 and BE3; each one received oral ketoconazole 50 mg/kg for fourteen days followed by: 200 mg/kg Eruca sativa (Gr. BC), 0.5 mg/kg oral sodium selenite (Gr. BD), 0.5 mg/kg/cm2 skin area local nanoselenium (Gr. BE1), 0.25 mg/kg oral nanoselenium (Gr. BE2) and 0.5 mg/kg oral nano selenium (Gr. BE3) respectively for 28 days. After this period, the animals were anesthetized, and plasma testosterone, luteinizing, and follicle stimulating hormones were assessed using Elisa Kit; after that, they were euthanized, and the epididymis of the right testis was carefully removed for evaluation of sperm indices (count, viability, abnormality, and motility). The reduction of selenium ions into PF-SeNPs induced by Eruca sativa extracts at a ratio of (1:2) (Na2SeO3: Eruca sativa) solution was confirmed by the gradual conversion of colour from dark brown to light yellow and then to reddish-orange after the addition of acidic sodium selenite solution and reacting for 12 h. The final reddish-orange colour is the most significant property of nanoparticles. In UV-vis spectroscopy, a strong absorption peak appeared between 268–964 nm with maxima at 268 nm, confirming the formation of nanoselenium. The optimal phytofabricated nanoselenium particles were obtained with a spherical shape, highly stable, and the smallest in size (39.4 nm in diameter) as proved by DLS with Poly Dispersity Index of 0.242 and zeta potential value of –56.57 mV. In the current study, testicles were damaged by administering ketoconazole at a dose of 50 mg/kg/day orally for 14 days. This testicular damage was linked to significant reductions in testosterone levels, elevated levels of LH and FSH, and significant decreases in sperm count, motility, and viability, which in turn affected spermatogenesis. Concurrently, the administration of Eruca sativa extract, sodium selenite and nanoselenium solution (in different doses and routes) following ketoconazole was shown to significantly improve biochemical parameters. These improvements included an increase in testosterone levels with little to no impact on LH and FSH levels as well as improved sperm indices. Additionally, the oral nanoselenium groups in 0.25 and 0.50 mg/kg produced the best outcomes with only minor differences between them. In conclusion, the antioxidant effects of the phytofabricated nanoselenium-based Eruca sativa leaf extract considerably improved testicular tissues.